What is Phase II NPDES? - Mark W. Clark (EDIS)
The Phase II program expands Phase I by requiring additional operators of MS4s in urban areas, and most industries and operators of small construction sites, to implement programs and practices to control polluted stormwater runoff through the use of NPDES permits. This document is SL 215, a fact sheet of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: February 2004.